2018
DOI: 10.1371/journal.pone.0202749
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new, efficient Mycobacterium tuberculosis topoisomerase-I inhibitors and their interaction with human ABC multidrug transporters

Abstract: Drug resistant tuberculosis (TB) is a major worldwide health problem. In addition to the bacterial mechanisms, human drug transporters limiting the cellular accumulation and the pharmacological disposition of drugs also influence the efficacy of treatment. Mycobacterium tuberculosis topoisomerase-I (MtTopo-I) is a promising target for antimicrobial treatment. In our previous work we have identified several hit compounds targeting the MtTopo-I by in silico docking. Here we expand the scope of the compounds arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In this study, we characterize Mes-Sa (human sarcoma) and A431 (human epidermoid carcinoma) cells, along with their transporter-expressing derivatives. In prior work our group has shown that both cell lines are suitable for the identification of cytotoxic MDR-substrates and MDR-selective compounds (Elkind et al 2005; Hegedűs et al 2009; Türk et al 2009; Nerada et al 2016; Füredi et al 2017; Szabó et al 2018; Temesszentandrási-Ambrus et al 2018). To evaluate the influence of OATP2B1 in the context of the MDR exporters, we wanted to use the same in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we characterize Mes-Sa (human sarcoma) and A431 (human epidermoid carcinoma) cells, along with their transporter-expressing derivatives. In prior work our group has shown that both cell lines are suitable for the identification of cytotoxic MDR-substrates and MDR-selective compounds (Elkind et al 2005; Hegedűs et al 2009; Türk et al 2009; Nerada et al 2016; Füredi et al 2017; Szabó et al 2018; Temesszentandrási-Ambrus et al 2018). To evaluate the influence of OATP2B1 in the context of the MDR exporters, we wanted to use the same in vitro model.…”
Section: Discussionmentioning
confidence: 99%
“…In silico virtual screening employing docking and molecular dynamics (MD) simulations can be used first to identify potential inhibitors from compound libraries, followed by biochemical assays on a small number of in silico hits with the highest predicted binding affinity to confirm the interaction and assess the topoisomerase inhibition and antimicrobial activity. This approach has been applied to identify inhibitors for E. coli and M. tuberculosis topoisomerase I using either crystal structures or target structures generated by computational modeling [ 94 , 95 , 96 , 97 , 98 ].…”
Section: Screening Approachesmentioning
confidence: 99%
“…The 639 compounds with MIC values < 6 μM were assayed for inhibition of M. tuberculosis topoisomerase I activity, and the results on the 108 compounds found to be active at 100 μM were used for building machine learning models for M. tuberculosis topoisomerase I inhibitors [ 97 ]. A selected set of seven Vichem NCL molecules with benzo(g)-quinoxaline, quinoxaline, or styryl-benzo(g)-quinazoline scaffolds was further characterized [ 98 ]. Cytotoxicity was measured against three human cell lines.…”
Section: Recent Attempts To Discover Novel Bacterial Topoisomerasementioning
confidence: 99%
See 2 more Smart Citations